Full-endoscopic spine surgery for intradural pathologies: A systematic review of innovations, challenges, and future prospects - Ilyas Dolas; Tugrul Cem Unal; Cafer Ikbal Gulsever; Duygu Dolen; Ali Guven Yorukoglu; Altay Sencer (Brain and Spine)
Introduction: Full-endoscopic spinal surgery (monoportal endoscopy) has emerged as a minimally invasive alternative for managing intradural spinal pathologies, offering reduced morbidity and accelerated recovery compared to conventional techniques. Research question: What is the current evidence on the effectiveness, limitations, and future prospects of full-endoscopic spinal surgery for intradural pathologies? Material and methods: A systematic review following PRISMA guidelines was conducted. Electronic databases (Cochrane, OVID-MEDLINE, PubMed, Embase, Web of Science, Scopus) were searched for studies published from 2000 to 2024. Studies on full-endoscopic intradural spine surgery, including clinical trials, comparative studies, case reports, and meta-analyses in English, were included. Exclusion criteria involved non-intradural pathologies, biportal techniques, animal studies, and non-English publications. Narrative synthesis was performed due to study heterogeneity. Results: Thirty studies were reviewed. Full-endoscopic techniques effectively managed conditions such as tethered cord syndrome, spinal arachnoid cysts, intradural extramedullary tumors, Chiari malformation, and select vascular and inflammatory conditions. Benefits included minimal tissue disruption, improved visualization, shorter hospital stays, and reduced complications. Key challenges identified were intraoperative bleeding control, reliable dural closure, and irrigation-related complications like increased intracranial pressure. Discussion and conclusion: Full-endoscopic spine surgery demonstrates substantial clinical promise for intradural spinal conditions, significantly reducing morbidity and enhancing recovery. However, addressing current technical challenges is essential. Ongoing technological advancements in imaging, neuronavigation, and robotic-assisted systems, combined with future clinical trials, will be critical for expanding indications and confirming long-term efficacy.